Phb Production Using Novel Agro-Industrial Sources From Different Bacillus Species. - BHAIRAVI GHATE; PRASHANT PANDIT; CHANDRASHEKHAR KULKARNI; DEEPTI D. MUNGI; TWISHA S. PATEL. (International Journal of Pharma and Bio Sciences, 2011)
For the production of polyhydroxybutyrate (PHB) different Bacillus species were isolated from soil samples. After the morphological and biochemical studies, isolates were identified as Bacillus cereus, Bacillus subtilis, and Bacillus megaterium. These Bacillus species were further explored for their potential to produce PHB using different low cost agro-industrial materials. PHB production was studied using agro-industrial materials like Jawar stem, Neera, Cashew apple pulp, Sugar cane bagasse, Coconut pulp and Grapes pulp. Extraction of PHB was done by hot chloroform method. PHB production was quantified using crotonic acid assay. Highest cellular PHB content was obtained from Bacillus subtilis with Neera as source of carbon which was found to be 0.284g/L. As Neera is a natural drink having very less shelf- life and majorly used for drinking purpose, its use in PHB production may prove beneficial, and hence may become an area of further research.